2019–2020 Florida Citrus Production Guide: Useful Websites and Mobile Apps - Jamie D. Burrow; Stephen H. Futch; Laurie Hurner; W. Chris Oswalt; Juanita Popenoe; Mongi Zekri (EDIS)
This 4-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. It contains a list of web-based programs that can be used to assist in the decision-making process of maintaining Florida citrus groves. The listing here does not indicate general or specific endorsement or exclusion of a product or service, nor does it indicate approval by the University of Florida, the Institute of Food and Agricultural Sciences, or the Florida Cooperative Extension Service. Written by Jamie D. Burrow, Stephen H. Futch, Laurie Hurner, Chris Oswalt, Juanita Popenoe, and Mongi Zekri, and published by the Horticultural Sciences Department, April 2019.